The effect of different rowing stroke rates on kinematics of lower extremity joints related to overuse injuries in professional teenager rowers: A cross-sectional study - Pakravan, F.; Abbasi, A.; Svoboda, Z.; Tazji, M. K. (Journal of Research in Rehabilitation, 2020)
Introduction: The purpose of this study was to determine the effects of different rates of rowing stroke on kinematics of lower extremity joints related to overuse injuries in professional teenager rowers.